Prevalence of drug misuse in Mexican elite athletes - Pegueros-Perez, A.; Ibarra-Ponce de Leon, J. C. (Archivos de medicina del deporte, 2008)
In Mexico, within the strategies of the National Antidoping Comitte for the fight and prevention of drug misuse in sports, it was implemented the antidoping controls in and out of competition, mainly in elite athletes whom are susceptible of falling in this inadequate practice. The increase on the number of controls out of competition has been an initial strategy to evaluate the effectiveness of the prevention programs and the results allow to reinforce or to improve these programs in those sports in which the adverse results are high. Objective: The purpose of this study was to evaluate the prevalence of drug misuse in Mexican elite athletes. Methods: It was done a retrospective analysis of the analytical results arisen from antidoping controls in and out of competition events of elite athletes in the years of 2003 to 2007. The information was evaluated with descriptive statistics and analysis of frequencies by Chi2. Results: Within the period of study 11,475 analyses were practiced and 4.4 % through an adverse result mainly in out of competition events. Taken into account all the adverse analytical findings, 50.1% corresponds to anabolic steroids, 32.6% to stimulants, 12.3% to cannabinoids and 5% to another pharmacological group. The substances with most prevalence were nandrolone, amphetamine, cannabis and ephedrine; the sport with high incidence is base ball and within this sport it has been an important reduction of this inadequate practice in the last two years. Conclusion: The misuse of drugs in Mexican elite athletes exists and it is most evident in professional sports like base ball. It is important to reinforce the information about the side-effects of the anabolic steroids and those considered as recreational drugs. These results are limited to elite sports and they might change when the educational programs apply to other levels inside sports